Aikaterini Koumarianou (Athènes, 1916-2012) - Balta, Evangelia; Chatziioannou, Maria Christina; Drakopoulou, Eugenia; Kallivretakis, Leonidas; Tolias, George (The Historical Review/La Revue Historique, 2013)
No abstract